1994
DOI: 10.1073/pnas.91.18.8617
|View full text |Cite
|
Sign up to set email alerts
|

The LIM protein RBTN2 and the basic helix-loop-helix protein TAL1 are present in a complex in erythroid cells.

Abstract: Chromosomal translocations in T-cell acute leukemias can activate genes encoding putative transcription factors such as the LIM proteins RBTN1 and RBTN2 and the DNA-binding basic helix-oop-helix transcription factor TALl associated with T-cell acute lymphocytic leukemia. While not expressed in normal T cells, RBTN2 and TALl are coexpressed in erythroid cells and are both important for erythroid differentiation. We demonstrate, using anti-RBTN2 and anti-TALl antisera, that the LIM protein RBTN2 is not phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
161
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 36 publications
2
161
0
2
Order By: Relevance
“…p300 can interact with transcription factors through either their transcriptional activation domains (Sartorelli et al, 1997;Sato et al, 1997) or their DNA-binding and dimerization domains Mutoh et al, 1998). Although TAL1 has been reported to possess a weak activation domain (Sa nchez-Garcõ a and Rabbitts, 1994;Wadman et al, 1994b), deletion analysis indicated that this region was dispensable for both Tal1-p300 interaction in solution (Figure 3b) and p300-stimulated transactivation ( Figure 5). TAL1 thus resembles E47 , BETA-2 (Mutoh et al, 1998), and possibly MyoD in that its bHLH domain can apparently mediate interaction with p300.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…p300 can interact with transcription factors through either their transcriptional activation domains (Sartorelli et al, 1997;Sato et al, 1997) or their DNA-binding and dimerization domains Mutoh et al, 1998). Although TAL1 has been reported to possess a weak activation domain (Sa nchez-Garcõ a and Rabbitts, 1994;Wadman et al, 1994b), deletion analysis indicated that this region was dispensable for both Tal1-p300 interaction in solution (Figure 3b) and p300-stimulated transactivation ( Figure 5). TAL1 thus resembles E47 , BETA-2 (Mutoh et al, 1998), and possibly MyoD in that its bHLH domain can apparently mediate interaction with p300.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to its E protein DNA-binding partners, recent studies have shown that the TAL1-encoded proteins can interact with the products of two genes, LMO1 and LMO2, that are themselves activated by chromosomal translocation in T-ALL (Valge-Archer et al, 1994;Wadman et al, 1994a). LMO1 and LMO2 contain tandem copies of a protein interaction motif termed the LIM domain and have each been shown to cooperate with TAL1 in inducing thymic neoplasms in bitransgenic mice (Aplan et al, 1997;Larson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of a T cell line with a t(11;14)(p15;q11), and expressing the LMO1 gene, showed that LMO1 interacts with at least two proteins in the nucleus of these cells; viz. TAL1/SCL and an uncharacterized 46 Kd protein (Valge-Archer et al, 1994). The ability of the LIM domains of LMO1 and LMO2 to act as surfaces for protein interaction (Valge-Archer et al, 1994;Wadman et al, 1994) provides a function for these zinc-containing modules and data on LMO2-containing protein complexes in erythroid cells (Wadman et al, 1994) and in T cell tumours arising in transgenic mice (Grutz et al, 1998) suggest that protein interaction, but not direct DNA binding, is the speci®c function of the LIM-only proteins LMO1 and LMO2.…”
mentioning
confidence: 99%
“…TAL1/SCL and an uncharacterized 46 Kd protein (Valge-Archer et al, 1994). The ability of the LIM domains of LMO1 and LMO2 to act as surfaces for protein interaction (Valge-Archer et al, 1994;Wadman et al, 1994) provides a function for these zinc-containing modules and data on LMO2-containing protein complexes in erythroid cells (Wadman et al, 1994) and in T cell tumours arising in transgenic mice (Grutz et al, 1998) suggest that protein interaction, but not direct DNA binding, is the speci®c function of the LIM-only proteins LMO1 and LMO2.Current molecular models propose that aberrant T cell-associated protein complexes, brought together by the LMO proteins after ectopic expression, contribute to tumorigenesis. The nature of the 46 Kd protein to which LMO1 binds is relevant to this issue because it is present in a complex with LMO1 in human T cell acute leukaemia line carrying the translocation t(11;15)(p15;q11).…”
mentioning
confidence: 99%